Spatio‐Temporal Convergence of Maximum Daily Light‐Use Efficiency Based on Radiation Absorption by Canopy Chlorophyll - Yao Zhang; Xiangming Xiao; Sebastian Wolf; Jin Wu; Xiaocui Wu; Beniamino Gioli; Georg Wohlfahrt; Alessandro Cescatti; Christiaan van derTol; Sha Zhou; Christopher M. Gough; Pierre Gentine; et al. (Geophysical Research Letters)
Abstract Light‐use efficiency (LUE), which quantifies the plants' efficiency in utilizing solar radiation for photosynthetic carbon fixation, is an important factor for gross primary production estimation. Here we use satellite‐based solar‐induced chlorophyll fluorescence as a proxy for photosynthetically active radiation absorbed by chlorophyll (APARchl) and derive an estimation of the fraction of APARchl (fPARchl) from four remotely sensed vegetation indicators. By comparing maximum LUE estimated at different scales from 127 eddy flux sites, we found that the maximum daily LUE based on PAR absorption by canopy chlorophyll ( εmaxchl), unlike other expressions of LUE, tends to converge across biome types. The photosynthetic seasonality in tropical forests can also be tracked by the change of fPARchl, suggesting the corresponding εmaxchl to have less seasonal variation. This spatio‐temporal convergence of LUE derived from fPARchl can be used to build simple but robust gross primary production models and to better constrain process‐based models.